The Interaction of Topicalization and Left-Dislocation in English - Betty J. Birner; Gregory Ward (Anglophonia)
Topicalization (TOP) in English requires that the topicalized information stand in a partially-ordered set (poset) relationship with previously evoked information, whereas Left-Dislocation (LD) has been argued to have three discourse functions: to simplify the processing of discourse-new information, to trigger a poset inference, or to amnesty an island violation (Prince 1997). In this paper, we examine naturally-occurring instances in which both constructions occur (e.g., ‘Scorpions, those you have to look out for’) and compare them to the corresponding variants with TOP only (‘Scorpions you have to look out for’) and LD only (‘Scorpions, you have to look out for those’). All of the LD+TOP tokens in our corpus are of Prince’s second type, inducing a poset inference. At issue is what motivates a speaker to use both constructions simultaneously, given that the discourse constraints of one subsume those of the other. We argue that there are two motivations, corresponding to two types of LD+TOP: One is to facilitate processing; the other is to effect contrast. In Type I, the fronted constituent is syntactically complex, with LD+TOP simplifying what would have been difficult to process as either LD or TOP alone. In Type II, an alternate member of the poset has been explicitly evoked and an open proposition (OP) is salient; here, LD+TOP serves a contrastive function, with both the preposed constituent and the focus of the OP being contrasted within their respective posets. Finally, whereas previous work has found that discourse functions behave compositionally, this study suggests that where compositionality is precluded, an additional function may be discerned, justifying the simultaneous use of multiple constructions.